Pembinaan Prestasi Ekstrakulikuler Basket SMAN di Kabupaten Pati Tahun 2019 (Indonesian Journal for Physical Education and Sport, 2020)
The objective of this study was to find out the basketball extracurricular coaching process in high schools in Pati Regency.This research used descriptive qualitative approach.The data collection was done by using observation, interview, and documentation methods. The subjects of this research were teachers as extracurricular coaches, trainers, and athetes/students. Data analysis technique used was data triangulation technique. The data analysis was done by reducing data, presenting data, and drawing conclusion.The result of this study showed that the coaching process of basketball extracurricular in High Shools in Pati Regency had been good enough. It could be seen from the mustering stage, training stage, and achievements stage, human resources, training programs, learning facilites, and the funding. From the result of this study, it could be concluded that the coaching process of basketball extracurrcular in high schools in Pati Regency had been good enough from the aspects of facilites, but the schools should increase the number of balls and fields that are needed in coaching process. In terms of the human resources, the trainers should attend the trainings that are held by PERBASI so that they have more certificates/licencies and get more experiences to train the students. The training program must be more detailed, clearly written, and can be a guideline in implementation of fostering achievement.